Systematic Literature Review for Smart Learning In Programming Courses - Al Farsi, Ghaliya; M. Tawafak, Ragad; Yaussef Alyoussef, Ibrahim; Mugahed Al-Rahmi, Waleed (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Advancements in technology are currently expediting the learning process for students, prompting an investigation into the integration of technology into student education. This study explores the impact of technological evolution on education. E-learning, a method of education that delivers information to students through modern communication platforms such as computers, networks, and multimedia audio components, is being examined. Whether utilized remotely or in traditional classroom settings, this revolution has made the world increasingly dependent on electronic screens in an era marked by the convergence of media technologies, information, culture, and technology. This paper outlines the development of an e-learning system customized for mobile devices, aimed at improving learning within the university environment. With mobile phones now ubiquitous among students, e-learning has become a potent tool for advancing educational objectives. Furthermore, e-learning aids in elevating student proficiency levels. The research conducted involved implementing and evaluating an application, which produced satisfactory results. As this application becomes integrated into university curricula to support learning, it is anticipated to substantially enhance students’ learning processes and performance, as evidenced by survey results following its implementation.